Domestic Violence Against Married Women in Rural Area of Wardha District: A Community Based Cross Sectional Study - Meenakshi P Khapre; Abhay B Mudey; Raviprakash D Meshram; Smrutiranjan C Nayak; Vasant V Wagh (Medsci Publications, 2014)
Background: Domestic violence against females is a serious public health concern in every community and culture. However, its actual extent is difficult to measure and may be much higher than reported. Long standing domestic violence not only affects the women physically but also has the long term impact on mental health. Domestic violence has the intergenerational cycle. As the rural women are more susceptible to domestic violence, present study would estimate the prevalence, associated vulnerability factors, and immediate reaction of women to domestic violence. Method: A community based cross-sectional study was planned in Sawangi Village of Wardha district. All the currently married women in 15-40 yrs were interviewed for domestic violence by male intimate partner in last 30 days. Data was then analyses by descriptive statistics. Result: One or other form of domestic violence was experienced by 68.12 % of study participants. More than two third were from nuclear family and Hindus by religion. Emotional violence was seen in 98 % of victims. Slapping was noted in all the victims of physical violence and nearly three fourth of them had sustained injuries. Alcohol was considered to be most common reason for domestic violence. Most of the victims had the feeling of revenge and powerlessness while 67 % of them resisted the act. Conclusion: The prevalence of domestic violence by spouse in last 30 days was very high in study population and it has greatly affected their mental health.